Lactoinduccion en novillas - Sanchez, L.=700 1 Luengas A.Z., A.; Mendez M., L.E.
(Es, En)
ilus., 21 ref.
Keywords: NOVILLA; LACTACION INDUCIDA; HORMONAS; ESTROGENOS; PROGESTERONA; QUISTES; PRODUCCION LECHERA; COLOMBIA; DEXAMETASONA